FEATURES OF THE SYNDROMES OF OSTEOPOROSIS AND SARCOPENIA IN RHEUMATOID ARTHRITIS WITH MUSCLE WEAKNESS (Spectrum Journal of Innovation, Reforms and Development, 2023)
Objective. The aim of the study was to evaluate the syndromes of sarcopenia (SP) and osteoporosis (OP) in RA patients with muscle weakness.